Chicory inulin enhances fermentation of 2′-fucosyllactose by infant fecal microbiota and differentially influences immature dendritic cell and T-cell cytokine responses under normal and Th2-polarizing conditions. Issue 19 (12th August 2021) - Akkerman, Renate; Logtenberg, Madelon J.; Beukema, Martin; de Haan, Bart J.; Faas, Marijke M.; Zoetendal, Erwin G.; Schols, Henk A.; de Vos, Paul
Abstract : Non-digestible carbohydrates (NDCs) such as native chicory inulin and 2′-fucosyllactose (2′-FL) are added to infant formula to mimic some of the human milk oligosaccharide (HMO) functions. Abstract : Scope : Non-digestible carbohydrates (NDCs) such as native chicory inulin and 2′-fucosyllactose (2′-FL) are added to infant formula to mimic some of the human milk oligosaccharide (HMO) functions. It is unknown whether combining inulin and 2′-FL influences their fermentation kinetics and whether the immune-modulatory effects of these NDCs are different under normal and inflammatory-prone Th2-polarizing conditions. Methods and results : We investigated the in vitro fermentation of 2′-FL and native chicory inulin, fermented individually and combined, using fecal inocula of 8-week-old infants. Native inulin was fermented in a size-dependent fashion and expedited the fermentation of 2′-FL. Fermentation of both native inulin and 2′FL increased the relative abundance of Bifidobacterium, which coincided with the production of acetate and lactate. The fermentation digesta of all fermentations differentially influenced both dendritic cell and T-cell cytokine responses under normal culture conditions or in presence of the Th2-polarizing cytokines IL-33 and TSLP, with the most pronounced effect for IL-1β in the presence of TSLP. Conclusions : Our findings show that native inulin can expedite the fermentation of 2′-FL by infant fecal microbiota and that these NDC fermentation digesta have different effects under normal and Th2-polarizing conditions, indicating that infants with different immune backgrounds might benefit from tailored NDC formulations.